Oversight of past legacy: reflections on Nepal’s draft water resources bill 2024 - KC, Sumitra; Onta, N. (International Water Management Institute, 2024)
Following a series of multistakeholder consultations, IWMI Nepal recommends that a comprehensive amendment of the Nepal Water Resources Bill 2024 is essential to address existing challenges, maximize the benefits of multipurpose use, and mitigate inconsistencies in sectoral planning.